A DESIGN OF "INTERACTIVE PAINTING WALL" MEDIA TO STIMULATE THE DEVELOPMENT OF EYE-HAND COORDINATION IN CHILDREN WITH MENTAL DISABILITIES OF ELEMENTARY SCHOOL AGE - siwi Anjarsari; Arry Mustikawan; Tsamarah Nadiyah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Children with intellectual disabilities at elementary school age require consistent developmental stimulation, particularly to strengthen hand-eye coordination. This ability serves as an important foundation for the development offine motor skills, concentration, and children’s independence in carrying out daily activities. However, learning media available in many educational institutions are often limited, less engaging, and have not fully provided structured visual-motor activities that suit children’s abilities. Therefore, this community service program aims to design and implement an “Interactive Painting Wall” as a medium to stimulate hand-eye coordination through color recognition activities andgradual painting movements. This medium is designed in the form of a patterned or thematic wall equipped with interactive elements, such as step markers, coloring areas, and simple visual instructions. The design is expected to helpchildren follow activity sequences more clearly, enjoyably, and with minimal dependence on verbal instructions. The implementation method includes partner needs analysis, media and visual material design, production and installation ofthe painting wall, trial use with the target children, and evaluation through structured observation. The evaluation focuses on several indicators of hand-eye coordination, including accuracy in following patterns, brush movement control, color suitability, and activity completion time. The outputs of this program include a ready-to-use Interactive Painting Wall, a brief user guide, and documentation of the implementation process and children’s developmental stimulationachievements. This program is expected to increase children’s engagement in learning activities, strengthen hand-eye coordination, and provide a sustainable learning medium to support the education of children with intellectual disabilitiesin the school environment.